2001
DOI: 10.1152/ajpcell.2001.281.1.c114
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency in parvalbumin increases fatigue resistance in fast-twitch muscle and upregulates mitochondria

Abstract: The soluble Ca2+-binding protein parvalbumin (PV) is expressed at high levels in fast-twitch muscles of mice. Deficiency of PV in knockout mice (PV -/-) slows down the speed of twitch relaxation, while maximum force generated during tetanic contraction is unaltered. We observed that PV-deficient fast-twitch muscles were significantly more resistant to fatigue than were the wild type. Thus components involved in Ca2+ homeostasis during the contraction-relaxation cycle were analyzed. No upregulation of another c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
63
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 37 publications
9
63
1
Order By: Relevance
“…Semiquantitative Western blot analysis of the mitochondrial protein COXI (Chen et al, 2001) was done in the forebrain of mice and confirmed our morphometric mitochondria data. In samples of mice ectopically expressing neuronal PV, the signal for COXI was weaker as compared to that from WT (Fig.…”
Section: Fractional Mitochondrial Area Of Neurons Ectopically Expresssupporting
confidence: 78%
See 1 more Smart Citation
“…Semiquantitative Western blot analysis of the mitochondrial protein COXI (Chen et al, 2001) was done in the forebrain of mice and confirmed our morphometric mitochondria data. In samples of mice ectopically expressing neuronal PV, the signal for COXI was weaker as compared to that from WT (Fig.…”
Section: Fractional Mitochondrial Area Of Neurons Ectopically Expresssupporting
confidence: 78%
“…Differences in COXI signal intensities were of smaller magnitude than changes in fractional area of neuronal mitochondria, as the whole tissue homogenate used to obtain the protein fraction contains not only neurons expressing the transgene, but also glial cells, endothelial cells, etc. It has recently been shown that in PV-knockout mice, mitochondria in fast-twitch muscles are up-regulated (Chen et al, 2001), indicating that in the absence of a diffusible buffer, mitochondria contribute to Ca 2+ buffering. A similar up-regulation also occurs in Purkinje cells of PV-KO mice, suggesting that a close link between PV levels and mitochondria volume is not restricted to muscle cells (B. Schwaller, in preparation).…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria participate in Ca 2ϩ removal during muscle relaxation in slow-twitch (Sembrowich et al, 1985;Gillis, 1997) and fast-twitch muscles (Rudolf et al, 2004); in neurons they also contribute to the presynaptic regulation of Ca 2ϩ transients (Billups and Forsythe, 2002). Besides the anticipated slowing of muscle relaxation in PVϪ/Ϫ mice, a twofold increase in mitochondrial volume density is observed that is viewed as a specific homeostatic compensation mechanism (Chen et al, 2001). Interestingly, the biochemical composition of PVϪ/Ϫ fast-muscle mitochondria is as found in slow-twitch muscles, characterized by higher expression levels of proteins involved in oxidative phosphorylation (Racay et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Such changes did not occur at the level of other Ca 2ϩ -binding proteins (CaBPs) (Schmidt et al, 2003b), but involved morphological alterations. An increase in PC spine length and volume was specifically induced by elimination of CB (Vecellio et al, 2000), while elimination of PV in fast-twitch muscles led to an approximately twofold increase in the mitochondrial volume density without affecting fiber surface size (Chen et al, 2001). We set out to test whether organelles (ER, mitochondria) implicated in Ca 2ϩ homeostasis in PC somata and dendrites are affected by elimination of cytosolic Ca 2ϩ buffers.…”
mentioning
confidence: 99%
“…In the absence of PV in PV 2/2 mice, an up-regulation of mitochondria occurs not only in PV-ergic Purkinje cells (Chen et al 2006) or cerebellar stellate and basket cells (B Schwaller, unpubl. ), but is also seen in PV 2/2 fast-twitch muscle fibers (Chen et al 2001). The latter are characterized by high PV expression levels in WT mice.…”
Section: Cytosolic Ca 2þ Buffersmentioning
confidence: 95%